VvPIP2;4N aquaporin involvement in controlling leaf hydraulic capacitance and resistance in grapevine. Issue 3 (8th June 2016) - Vitali, Marco; Cochard, Hervé; Gambino, Giorgio; Ponomarenko, Alexandre; Perrone, Irene; Lovisolo, Claudio
Abstract : Hydraulic capacitance (C) in a plant tissue buffers the xylem tension, storing and releasing water and has been highlighted in recent years as an important factor that affects water relations such as drought tolerance and embolism formation. Aquaporins (AQPs) are well known to control leaf hydraulic resistance (Rh) but their role in the control of C is unknown. Here, we assess Rh and C on detached grapevines wild‐type (WT) (cv. Brachetto) leaves and over‐expressing the aquaporin gene VvPIP2;4N (OE). For this purpose, we developed a new method inspired from the pressure‐volume curve technique and the rehydration‐kinetic‐method, which allowed us to monitor the dynamics of dehydration and rehydration in the same leaf. The recovery after dehydration was measured in dark, light non‐transpirative conditions, light‐transpirative conditions and light‐transpirative condition adding abscisic acid. Pressurizing to dehydrate leaves in the OE line, the recorded Rh and C were respectively lower and higher than those in the WT. The same results were obtained in the dark recovery by rehydration treatment. In the presence of light, either when leaves transpired or not (by depressing vapor pressure deficit), the described effects disappeared. The change in Rh and C did not affect the kinetics of desiccation of detached leaves in dark in air, in OE plants compared to WT ones. Our study highlighted that both Rh and C were influenced by the constitutive over‐expression of VvPIP2;4N . The effect of AQPs on C is reported here for the first time and may involve a modulation of cell reflection coefficient.